Enhancing cancer immunotherapy with photodynamic therapy and nanoparticle: making tumor microenvironment hotter to make immunotherapeutic work better - Thiruppathi, Jayalakshmi; Vijayan, Veena; Park, In-Kyu; Lee, Shee Eun; Rhee, Joon Haeng (Frontiers in Immunology, 2024)
Cancer immunotherapy has made tremendous advancements in treating various malignancies. The biggest hurdle to successful immunotherapy would be the immunosuppressive tumor microenvironment (TME) and low immunogenicity of cancer cells. To make immunotherapy successful, the 'cold' TME must be converted to 'hot' immunostimulatory status to activate residual host immune responses. To this end, the immunosuppressive equilibrium in TME should be broken, and immunogenic cancer cell death ought to be induced to stimulate tumor-killing immune cells appropriately. Photodynamic therapy (PDT) is an efficient way of inducing immunogenic cell death (ICD) of cancer cells and disrupting immune-restrictive tumor tissues. PDT would trigger a chain reaction that would make the TME 'hot' and have ICD-induced tumor antigens presented to immune cells. In principle, the strategic combination of PDT and immunotherapy would synergize to enhance therapeutic outcomes in many intractable tumors. Novel technologies employing nanocarriers were developed to deliver photosensitizers and immunotherapeutic to TME efficiently. New-generation nanomedicines have been developed for PDT immunotherapy in recent years, which will accelerate clinical applications.